Math

(2/9)^3×(2/9)^(-6)=(2/9)^(2m-1)

  1. 👍 0
  2. 👎 0
  3. 👁 138
  1. Hmmm. I thought Reiny already showed how to do this one.
    (2/9)^3×(2/9)^(-6)=(2/9)^(2m-1)
    (2/9)^(3-6) = (2/9)^(2m-1)
    -3 = 2m-1
    m = -1

    It's better to use * for multiplication online, since the variable x is easy to confuse with ×

  2. if the bases are the same , you can add the exponents

    (2/9)^3 × (2/9)^(-6) = (2/9)^(3-6) = (2/9)^(-3)

    (2/9)^(-3) = (2/9)^(2m - 1)

    1. 👍 1
    2. 👎 0

Respond to this Question

First Name

Your Response